Privacy & Security Concerns in Digital advertising: A Critique - Rajat Verma, Charu Awasthi, Prashant Kumar Mishra (International Journal of Advanced Science and Technology, 2020)
In today’s digital era, we use numerous platforms for social, marketing and learning purposes. We give permissions to these online platforms to access our personal data. This data may be sensitive or insensitive depending on a particular user. In most cases, users become careless and do not read the terms and conditions of diverse products/goods or advertising mechanisms. In current decade, immense exposure to cybercrimes has grown and will continue until its saturation point comes. So, the data must be kept protected to the best of the knowledge of an individual. The promoters/advertisers are well prepared for any exception to happen and they know plenty of tools and tactics to target the users. Fake advertisements are also in use and the people get easily fooled by these intentional attackers. In this paper, the unsafe approaches for use of various application software and services are illustrated with the importance of marking the checkboxes after reading the text properly.